2019
DOI: 10.1096/fj.201801111rr
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA AK089579 inhibits epithelial‐to‐mesenchymal transition of peritoneal mesothelial cells by competitively binding to microRNA‐296‐3p via DOK2 in peritoneal fibrosis

Abstract: Peritoneal fibrosis (PF) represents a well‐recognized complication associated with continuous ambulatory peritoneal dialysis therapy, characterized by a reversible epithelial‐to‐mesenchymal transition (EMT) at the early stage. The aim of the current study was to investigate the effects linked with the long noncoding RNA (IncRNA) AK089579 on the EMT of peritoneal mesothelial cells (PMCs) as well as the associated regulatory mechanisms of AK089579 downstream of tyrosine kinase 2 (DOK2) and microRNA‐296‐3p (miR‐2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…Another study found that DOK2 deletion is associated with mutations in EGFR in human lung adenocarcinoma, jointly promoting tumor development (19). In addition, DOK2 can be used as a poor prognostic marker for human glioblastoma multiforme and can inhibit tumor migration and invasion via the JAK2/STAT3 pathway (20,21). In our study, in addition to the signi cant survival correlation between DOK2 and lung adenocarcinoma, DOK1 and DOK6 were also signi cantly associated with lung adenocarcinoma.…”
Section: Discussionsupporting
confidence: 63%
“…Another study found that DOK2 deletion is associated with mutations in EGFR in human lung adenocarcinoma, jointly promoting tumor development (19). In addition, DOK2 can be used as a poor prognostic marker for human glioblastoma multiforme and can inhibit tumor migration and invasion via the JAK2/STAT3 pathway (20,21). In our study, in addition to the signi cant survival correlation between DOK2 and lung adenocarcinoma, DOK1 and DOK6 were also signi cantly associated with lung adenocarcinoma.…”
Section: Discussionsupporting
confidence: 63%
“…Increasing evidence have indicated lncRNAs' involvement in the pathogenesis of many diseases, including fibrosis [32][33][34]. Previous studies have showed that lncRNA PFAL contributed to the progression of pulmonary fibrosis [35].…”
Section: Agingmentioning
confidence: 99%
“…113 Zhang et al reported that lncRNA AK089579 had the ability to inhibit EMT, migration, and invasion of MCs, due to the competitive integration with miRNA-296-3p through DOK2 and JAK2/STAT3 signaling pathways. 78 Except for lncRNA AK089579, AV310809, uc007eib.1, AK142426, and ENSMUST00000053838 were upregulated in the fibrotic peritoneum, while others were demonstrated to be downregulated, such as uc007dlv.1, AK080622, BC049991, and uc008pwj.1. 94,110 This demonstrates close contact between lncRNAs and PF.…”
Section: Epigenetic Modulation During Pdmentioning
confidence: 98%
“…Through gene intersection association analysis, they found miR-296-3p can bind to lncRNA AK089579 competitively and upregulate the expression of target gene DOK2 consequently, thereby inhibiting PF by suppressing the activation of the JAK2/STAT3 signaling pathway. 78 Si et al developed a therapeutic strategy to target hyperglycolysis and fibrotic signaling during the development of PF induced by PDF in mice. They designed a triad of adeno-associated viruses that overexpressed miRNA-26a and miRNA-200a while inhibiting miRNA-21a.…”
Section: Epigenetic Modulation During Pdmentioning
confidence: 99%